The Influence Of Health Promotion Using Lecture Method Using Comic Media On Dental And Oral Health Knowledge In Class III Students At State Primary School 1 Pangkajene District Sidenreng Rappang - Rezki Dirman; Utari Zulkaidah; Sultan Amin Yasin; Yulistina (Sahabat Publikasi Kuu, 2024)
Introduction: Dental and oral health has a big influence on preventing cavities or caries, gingivitis, perioldolitis, and also preventing bad breath. Diseases affecting the teeth and mouth, causing complaints of pain. School-aged children 6-12 years old are the age category at risk of developing cavities or caries. Age 6-12 years is the age when milk teeth begin to replace permanent teeth. One of the causes of the prevalence of dental and oral diseases in Indonesian children is the low level of knowledge about dental and oral health. Objective: to determine the effect of health promotion using the lecture method using kolmik media on dental and oral health knowledge in class III students at Pangkajene 1 Elementary School, Sidenreng Rapang Regency. Method: This type of research is quantitative research with a research design using a pre-experimental design, namely Olne Group Pretest and Polstest. The sample used was 31 people taken using the Total Sampling technique. Results: Before being given health promotion using the lecture method using comic media with a number of 54 with poor criteria and after being given health promotion using the lecture method using comic media with a number of 80 with good criteria. There was a level of increase in knowledge, namely 26. And the significance value was using the Paired T Test. namely 0.01 < 0.05 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted